The Effect of Company Size, Sales Growth, Profitability and Leverage on Stock Returns in Food And Beverage Companies Listed on the Indonesia Stock Exchange (IDX): Pengaruh Ukuran Perusahaan, Pertumbuhan Penjualan, Profitabilitas Dan Leverage Terhadap Return Saham Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Okta, Selly; Hariasih, Misti (Indonesian Journal of Innovation Studies, 2021)
Important information for investors in making investment decisions is reflected in the financial statements. Investors certainly expect a high rate of return from the funds they invest in the company. The purpose of this research is to determine The influence of Company Size, Sales Growth, Prifitability, and Leverage on Food and Beverage Companies Listed on the Indonesia Stock Exchange 2015 - 2019. Through the criteria in the purposive sampling method, a sample of 11 companies in the food and beverages sector was obtained. Panel data regression analysis technique is regression by combining cross-section and time-series data at the same time in an equation. The panel data will be analyzed using Eviews 10. And get the results that (1) Company size (Size) affects stock returns, (2) Sales growth (Growth) affects stock returns, (3) Profitability (ROA) affects stock returns and Leverage (DER) affects stock returns .